PENGARUH MOTIVASI KERJA TERHADAP KINERJA AUDITOR ( STUDI PADA INSPEKTORAT KOTA KENDARI ) - Husin, Husin; Umbara, Bayu (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACT This research aimed to determine the effect of the significant Work Motivation on Auditors Performance in Inspektorat Kota Kendari. In this study, the data sources used are primary data and secondary data. The method used in this research is descriptive and analytical methods of inferential analysis method consisting of factor analysis and simple linear regression analysis. The result of this study indicate that the Work Motivation significantly influence the Auditors Performance in Inspektorat Kota Kendari, that are proven with probability value = 0,000 < 0,05. Then the hypothesis is accepted.Key Words : Work Motivation and Auditors Performance.